2019
DOI: 10.1523/eneuro.0338-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Reward Devaluation Attenuates Cue-Evoked Sucrose Seeking and Is Associated with the Elimination of Excitability Differences between Ensemble and Non-ensemble Neurons in the Nucleus Accumbens

Abstract: Animals must learn relationships between foods and the environmental cues that predict their availability for survival. Such cue-food associations are encoded in sparse sets of neurons or "neuronal ensembles" in the nucleus accumbens (NAc). For these ensemble-encoded, cue-controlled appetitive responses to remain adaptive, they must allow for their dynamic updating depending on acute changes in internal states such as physiological hunger or the perceived desirability of food. However, how these neuronal ensem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…On test day, our mice did not directly experience sucrose reward. However, we and others have shown that conditioned approach responses evoked by Pavlovian sucrose cues are under the control of retrieving a representation of the sucrose reward, as it is sensitive to devaluation manipulations ( Sieburg et al, 2019 ). From this perspective, our mice may have attributed greater reward value to the recent EE experience compared with the retrieved representation of sucrose, thus resulting in a negative contrast effect ( Grimm & Sauter, 2020 ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…On test day, our mice did not directly experience sucrose reward. However, we and others have shown that conditioned approach responses evoked by Pavlovian sucrose cues are under the control of retrieving a representation of the sucrose reward, as it is sensitive to devaluation manipulations ( Sieburg et al, 2019 ). From this perspective, our mice may have attributed greater reward value to the recent EE experience compared with the retrieved representation of sucrose, thus resulting in a negative contrast effect ( Grimm & Sauter, 2020 ).…”
Section: Discussionmentioning
confidence: 93%
“…Following acquisition of this simple CS-US association, sucrose-seeking behavior is assessed by measuring approach and responding (i.e. head entry) to the sucrose delivery site during the (non-reinforced) sucrose-associated CS ( Blaiss & Janak, 2009 ; Day et al, 2006 ; Sieburg et al, 2019 ; Ziminski, Hessler, et al, 2017 ). Next, because Fos expression increases in different corticoaccumbens areas in response to non-contingent food CS exposure ( Brebner et al, 2020 ; Haight et al, 2017 ; Schroeder et al, 2001 ; Ziminski, Hessler, et al, 2017 ), we compared “Fos” expression across different EE conditions in the medial prefrontal cortex (mPFC), orbitofrontal cortex (OFC), and nucleus accumbens (NAc).…”
Section: Introductionmentioning
confidence: 99%
“…Goal-directed behaviors and habits can be quickly and e ciently developed by the random ratio (RR) task with effort-based reward delivery and the random interval (RI) task with time-based reward delivery 4 . We used sucrose solution as a reward since it has an intense rewarding effect in mice, especially in operant conditioning [13][14][15] . Upon nose-poke in an active hole, 10 µl of 20% sucrose solution was immediately delivered in the magazine through an automated syringe as we previously described [16][17][18] .…”
Section: Resultsmentioning
confidence: 99%
“…As previously described 17,18 , we utilized sucrose as a reward. After fasting, mice are highly motivated to seek out sucrose, which facilitates the operant learning 14 . Although sucrose is not fully representing the addictive drugs 50 , sucrose has common rewarding and reinforcing properties as substance abuse, especially in rodents 15,51 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to lever pressing, head entry to the food magazine has been used to assess flexibility (DePoy et al, 2016; Morrison et al, 2015; Sieburg et al, 2019). ChR2 mice and YFP controls both altered their entry rates across training (two-way repeated measures ANOVA, significant effect of time, F (14, 392) = 5.148, p <0.0001), though ChR2 mice tended to have higher entry rates (trending effect of group, F (1, 28) = 3.204, p = 0.0843; no significant interaction, p > 0.05; Figure 2F).…”
Section: Resultsmentioning
confidence: 99%